Evaluation of SongketChain : A Framework to Protect Unique Cultural Product using Blockchain Technology - Muhammad Hassif Imran, Muhammad Harris Irwan; Johari, Abdullah; Adnan Shahid, Khan; Nayeem Ahmad, Khan (Semarak Ilmu Publishing, 2025)
The traditional art of Songket weaving in Sarawak, Malaysia, embodies a rich cultural heritage that has faced threats from counterfeit practices, undermining the authenticity and economic value of this artisan craft. In response, this research introduces SongketChain, a blockchain-based framework aimed at preserving the originality and enhancing the traceability and transparency of Songket production. By leveraging both public and private blockchain technologies, SongketChain offers a novel approach to securing pattern rights and supply chain logistics, ensuring that each Songket product's journey from weaver to consumer is documented and verifiable. This study evaluates the effectiveness of SongketChain through a comparative analysis of blockchain platforms and consensus algorithms, highlighting the framework's potential to mitigate counterfeit issues and support the sustainable development of the Songket market. The findings demonstrate that blockchain technology can play a crucial role in protecting cultural heritage, offering a replicable model for other traditional crafts facing similar challenges. This research contributes to the discourse on the application of blockchain in cultural preservation and supply chain management, laying the groundwork for future explorations into its broader implications for the artisan sector. Quantitatively, the study showcases a 100% improvement in transparency and traceability across the Songket supply chain, effectively integrating over 12 unique data points per product to authenticate and secure the Songket production process from inception to customer delivery.